Molecular approach for identification of fungi from soils of Cameron Highlands (Journal of Biochemistry, Microbiology and Biotechnology, 2014)
Seven cultures of fungi were isolated from the soil of Cameroon Highlands. In this research, molecular approach was used for the identification of these fungi. The genomic DNA of the fungi species was extracted and the target sequences within the DNA were amplified using polymerase chain reaction (PCR) with ITS 1 (forward) and ITS 4 (reverse) as the primers which amplified the Internal Transcribe Spacer (ITS) of the fungi. The size of PCR product was 600 base pairs. The PCR products were purified and the DNA purity obtained for culture 1, 2, 3 and 4 were 1.74, 1.92, 1.83 and 1.77, respectively. Based on the sequences of the PCR products, three species were successfully identified as Aspergillus flavus, Aspergillus niger and Fusarium oxysporum.Â